Studi Komparatif Teologi Cyrill Tentang Kebangkitan Kristus dan Budaya Slametan Suku Jawa: Sebagai Jembatan Misi - Eka Kurniawan Zebua (Predica Verbum: Jurnal Teologi dan Misi, 2025)
This study aims to explore the encounter between Cyrill's theology and the Slametan culture of the Javanese tribe. Cyril is one of the important figures in the history of the Church who has made a significant contribution to understanding the meaning of the resurrection of Jesus Christ. For Cyrill, the resurrection is not merely a historical event, but has profound theological implications for the lives of believers. The resurrection of Christ is an absolute gift of victory for human life over sin and death, so that through His resurrection, it becomes clear evidence that true salvation comes only from Him who is full of power. This study provides a new contribution to understanding the dynamics between the Christian faith and local culture by focusing on the concept of Christ's resurrection and the practice of selametan. This study uses a literature review and qualitative analysis approach to compare the concept of Christ's resurrection and the practice of selamatan. By examining various sources, including sacred texts, theological literature, and ethnography, this study provides a comprehensive understanding of the interaction between faith and culture. This study contributes a methodology that can be applied in similar studies on religion and culture. It highlights the importance of dialogue between theology and cultural anthropology in the context of religious pluralism in Indonesia and is a first step toward carrying out a mission for the Javanese people.